S.Sos - Dinda Maghfirah (At-Taujih : Bimbingan dan Konseling Islam, 2022)
Abstract: This research is motivated by the issue of sexual violence against children that continues to occur in Indonesia, especially in the city of Lhokseumawe. Integrated Service Center For The Empowerment Of Women And Children Lhokseumawe City as a service forum for women and children must optimize its role in efforts to fulfill information and needs in the fields of Education, Health, Economy, Politics, Law, Protection and Prevention of acts of violence, and trafficking of women and child. The research method used in this research is descriptive qualitative, namely a research procedure that produces descriptive data in the form of written and spoken words from people and observed behavior. This research was conducted to find out the counseling services obtained by child victims of sexual violence in the mentoring process carried out by the Integrated Service Center for Women and Children the research results show that: 1). The role of the Lhokseumawe City Women and Children Empowerment Integrated Service Center is to provide assistance services, in the form of: legal assistance services, medical assistance services, psychological assistance services. 2). Inhibiting factors for the Integrated Service Center for the Empowerment of Women and Children in Lhokseumawe City, in the form of: lack of psychological Human Resources, traumatic victims, lack of budget, negative perceptions of victims, public apathy, lack of facilities and infrastructure.Keywords: Integrated Service Center For The Empowerment Of Women And Children, Counseling Service, Sexual Violence, Children Abstrak: Penelitian ini dilatarbelakangi oleh isu kekerasan seksual terhadap anak yang terus terjadi di Indonesia khususnya di kota Lhokseumawe. Pusat Pelayanan Terpadu Pemberdayaan Perempuan Dan Anak (P2tp2a) Kota Lhokseumawe sebagai wadah pelayanan perempuan dan anak harus mengoptimalkan perannya dalam upaya pemenuhan informasi dan kebutuhan di bidang Pendidikan, Kesehatan, Ekonomi, Politik, Hukum, Perlindungan dan Pencegahan tindak kekerasan, dan perdagangan perempuan dan anak. Metode penelitian yang digunakan dalam penelitian ini adalah deskriptif kualitatif, yaitu suatu prosedur penelitian yang menghasilkan data deskriptif berupa kata-kata tertulis dan lisan dari orang-orang dan perilaku yang diamati. Penelitian ini dilakukan untuk mengetahui layanan konseling yang diperoleh anak korban kekerasan seksual dalam proses pendampingan yang dilakukan oleh Pusat Pelayanan Terpadu Perempuan dan Anak (P2TP2A). Hasil penelitian menunjukkan bahwa: 1). Peran Pusat Pelayanan Terpadu Pemberdayaan Perempuan dan Anak (P2TP2A) Kota Lhokseumawe adalah memberikan pelayanan pendampingan, berupa: pelayanan bantuan hukum, pelayanan bantuan medis, pelayanan pendampingan psikologis. 2). Faktor penghambat Pusat Pelayanan Terpadu Pemberdayaan Perempuan dan Anak (P2TP2A) Kota Lhokseumawe, berupa: kurangnya Sumber Daya Manusia (SDM) psikologis, trauma korban, keterbatasan anggaran, persepsi negatif terhadap korban, sikap apatis masyarakat, kurangnya sarana dan prasarana..Kata kunci : Pusat Pelayanan Terpadu Pemberdayaan Perempuan Dan Anak (P2TP2A) Kota Lhokseumawe, Layanan Konseling, Kekerasan Seksual, Anak